Correction: Resonance Raman spectroscopy as an in situ probe for monitoring catalytic events in a Ru-porphyrin mediated amination reaction. Issue 19 (1st September 2016) - Zardi, Paolo; Gallo, Emma; Solan, Gregory A.; Hudson, Andrew J.
Abstract : Correction for 'Resonance Raman spectroscopy as an in situ probe for monitoring catalytic events in a Ru-porphyrin mediated amination reaction' by Paolo Zardi et al., Analyst, 2016, 141, 3050–3058.